Recovery of highly-dispersive modes using a wavelength-resolved modified S 2 imaging method - Lamilla, Erick; Aldaya, Ivan [UNESP]; Faria, Maicon S.; Jarschel, Paulo F.; Pita, Julián L.; Dainese, Paulo (Optica Publishing Group, 2018)
We present a modified w avelength-resolved S 2 m ethod t hat a llows r ecovery of highly-dispersive modes. We employed this method using a variable window spectrogram to characterize a hollow core photonic crystal fiber where several surface-modes are recovered.